Implementation of Betty Neuman's Systems Theory in Hospital Nursing Practice: A Systematic Review - Umi Laila; Fery Agusman Motuho Mendrofa; Tri Ismu Pujianto (Indonesian Journal of Global Health Research, 2025)
Betty Neuman's system theory offers a holistic nursing approach that focuses on strengthening the patient's line of defense through the identification and management of stressors at the primary, secondary, and tertiary levels. Although this model has been widely applied in clinical practice, the consistency and effectiveness of its implementation in hospitals still require thorough evaluation. This study aims to systematically review empirical evidence on the application of Betty Neuman's theory in the field of nursing in hospitals. The method used in writing this article is a literature study with a systematic review method. The articles reviewed were obtained through searches on Google Scholar, Sematic Scholar, Proquest, and ScienceDirect in the period 2015-2025 with the search keywords implementation, nursing, hospital, betty neuman system Using PRISMA, from 946 articles found, 10 journal articles were obtained for review. A total of 10 articles were synthesized based on the findings of the effectiveness of implementing Betty Neuman's theory in nursing practice in hospitals, including Environmental Factors, Client System, Stressors, Lines of Defense and Resistance, Three Levels of Prevention, and Recovery. The results of the study indicate that the implementation of this theory is effective in strengthening the patient's defense system, reducing anxiety levels, and accelerating recovery in various conditions such as stroke, cancer, heart failure, and pre-operative anxiety. This model facilitates a multidimensional approach that includes the physiological, psychological, social, and spiritual aspects of the patient, while emphasizing the role of nurses as stressor managers and holistic recovery facilitators. However, practice in the field is still often limited to physical interventions only, so that the full potential of the theory has not been optimally utilized.